2018
DOI: 10.1016/j.biopsycho.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Detached and distracted: ERP correlates of altered attentional function in depersonalisation

Abstract: Depersonalisation (DP) is a psychological condition marked by feelings of disembodiment. In everyday life, it is frequently associated with concentration problems. The present study used visual event-related potentials (ERPs) in a Posner-type spatial cueing task with valid, invalid and spatially neutral cues to delineate the potential neurophysiological correlates of these concentration problems. Altered attentional functioning at early, sensory stages was found in DP patients but not in anxiety- and depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…One interesting question is whether the lack of the typical self-bias in VRT found in those with a high occurrence of DP is due to bottom-up impairments in multisensory integration of self-related information or whether this process is driven by top-down inhibition. In the first case the lack of a VRT effect for the self would be closely related to the findings of anomalous processing in brain regions involved in sensory integration (Simeon et al, 2000) or in attentional processing (Adler et al, 2014;Giesbrecht et al, 2008;Schabinger et al, 2018) in DP. On the second account, advantages due to self-processing may be inhibited due to conflict between explicit selfrecognition and feelings of detachment from the observed self-face.…”
Section: Effect Of Depersonalisation On Self-bias In Visual Remappingmentioning
confidence: 82%
“…One interesting question is whether the lack of the typical self-bias in VRT found in those with a high occurrence of DP is due to bottom-up impairments in multisensory integration of self-related information or whether this process is driven by top-down inhibition. In the first case the lack of a VRT effect for the self would be closely related to the findings of anomalous processing in brain regions involved in sensory integration (Simeon et al, 2000) or in attentional processing (Adler et al, 2014;Giesbrecht et al, 2008;Schabinger et al, 2018) in DP. On the second account, advantages due to self-processing may be inhibited due to conflict between explicit selfrecognition and feelings of detachment from the observed self-face.…”
Section: Effect Of Depersonalisation On Self-bias In Visual Remappingmentioning
confidence: 82%
“…Reduced brain activities have been observed in DPD patients in sensory information processing units (Medford et al, 2016) as well as regions responsible for the processing of visceral signals (Lemche et al, 2013). Besides, the impairment is found mainly in the early stages of information processing (Adler et al, 2016;Quaedflieg et al, 2013;Schabinger et al, 2018). This impairment in the implicit processing of multimodal interoceptive and exteroceptive signals could be a result of long-time severe stress or anxiety (Shilony and Grossman, 1993), which may damage the sensory processing units and reduce their processing capacity (Sierra and Berrios, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…No such reduction in P300 latency was observed in the comparison between panic disorder patients without depersonalisation and the control group. In addition to the unchanged attentional effects at P300 in a visual-spatial task comparing DPD with psychosomatic control patients (Schabinger et al, 2018), longer (rather than reduced) P300 latencies were reported in panic disorder patients compared to healthy individuals (Turan et al, 2002). In sum, although P300 may be a valuable electrophysiological biomarker for attentional deficits in depersonalisation/derealisation, more studies with carefully designed tasks are needed to examine its precise expression in each task and for each group of patients.…”
Section: Other Symptoms Of Dpdmentioning
confidence: 98%
“…Our study contributes to this literature by showing that individuals with better interoceptive abilities, specifically the ability to sustain and control attention to bodily signals, also have stronger vicarious representations of observed touch within somatosensory cortices. Depersonalization, which is characterized by a disrupted relationship with the bodily self, is also marked by altered attentional processing, and it has recently been shown that these alterations occur at early cortical processing stages (Schabinger et al, ). This indicates that alterations in the sense of bodily self might be accompanied by alterations in the ability to selectively allocate attention to bodily or environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%